Hyperbaric pressure at room temperature increases post-harvest preservation of the tomato cultivar ‘Débora’ - Inestroza-Lizardo, Carlos [UNESP]; Mattiuz, Ben-Hur [UNESP]; da Silva, Josiane Pereira; Galati, Vanessa Cury; Voigt, Vanessa [UNESP] (Elsevier, 2018)
The aim of the present study was to evaluate the effect of the application of hyperbaric pressure at room temperature (23 ± 1 °C) for 2, 4 or 6 d, followed by 2 d under ambient conditions (23 °C, 50% relative humidity, 100 kPa), on the physical, chemical and metabolic characteristics of the tomato cultivar ‘Débora’. The following pressures were tested: 100 (control), 200, 400, 600 and 800 kPa. Tomatoes subjected to 600 or 800 kPa for 6 d presented lower weight loss (up to 80%) and 1.2 times greater firmness than control tomatoes. Hyperbaric pressure did not decrease the tomato respiration rate. However, the initial tomato color was maintained with increasing applied pressure, and pressure decreased tomato lycopene synthesis by up to 57%. Normal tomato ripening was not negatively affected by the application of hyperbaric pressure. The present results show that application of hyperbaric pressure up to 800 kPa at 23 °C delays the ripening of the tomato cultivar ‘Débora’ and results in longer shelf life.
Keywords: Color; Firmness; Lycopene; Ripening; Solanum lycopersicum L